Double Diffusion Mixed Convection in a Porous Cylindrical Cavity Filled with a Casson Nanofluid Driven by a Lid, Taking Into Account the Soret and Dufour Effects - Mustapha El Hamma; Lebna Elattari; Soufiane Nouari (Journal of Heat and Mass Transfer Research)
The aim of this study is to analyze and calculate the thermosolutal mixed convection in a porous cylindrical cavity containing a Casson nanofluid (aluminum nanoparticle). This research was conducted under Darcy regime conditions with . Analysis is carried out for a range of model factors, including Richardson’s number (0.1 to 1), Reynolds number (1 to 9), porosity (0.1 to 1), Soret and Dufour numbers (0.1 to 1), Casson fluid parameter (0.1 to 0.5), Buoyancy ratio (1 to 10), Prandtl number (1 to 10), and Geometric aspect ratio (2 to 3). The volume fraction of nanoparticles was set at % for the flow of Casson nanofluid through porous layers, as explained by the extended Brinkman-Forchheimer DARCY law. As we note in this research that the thermosolutal transfer decreases with the increase in Richardson number in the case of  >10, and the thermosolutal transfer increases with the increase in casson fluid parameter; on the contrary we notice that the transfer of heat decreases with the increase in the Soret and Dufour numbers, and at the end we find that thetmosolutal transfer increases with the increase in Reynolds number in the Dacian regime. Numerical simulations were conducted using numerical methods rooted in the finite volume method (FVM). Fortran numerical codes using FVM were implemented in the experiments to achieve the results. Therefore, we examined how various factors impact both heat transfer and concentration rates.